Digital Infrastructure as a Strategy for Strengthening the Rattan SME Industry - Anisa Ayu Dwi Lestari; Aisyah Nurjanah (Cakrawala Repositori IMWI)
The rattan industry in Cirebon faces a paradox between substantial economic potential and low digital technology adoption, with only 18% of SMEs active on e-commerce platforms. This study aims to analyze the role of digital infrastructure as a strategy for economic empowerment of rattan SMEs in Cirebon, identify factors influencing digital adoption, and develop contextually appropriate implementation models. Employing a mixed-method sequential explanatory design, the research involved 218 SME respondents through stratified random sampling surveys and 15 key informants through in-depth interviews. Quantitative data were analyzed using SPSS (descriptive statistics, t-tests, multiple regression), while qualitative data were analyzed with thematic analysis. Results reveal that digital adopter SMEs demonstrate 77.7% higher revenue, 583% wider market reach, and 47.4% greater profit margins compared to non-adopters (p<0.001). Significant factors influencing adoption include digital literacy (?=0.412), perceived ease of use (?=0.337), and financial capability (?=0.289), explaining 68.4% of digital adoption variance. Multi-platform strategy yields 94% success rate with 142% revenue growth. The study identifies a heritage-digital integration framework enabling SMEs to preserve cultural values while enhancing competitiveness. Practical implications include developing Digital Hubs, peer-to-peer Digital Mentor programs, and Pay-as-You-Grow policies to address digital literacy barriers (78%) and financial constraints (65%). Findings contribute to craft industry digital transformation literature and provide actionable roadmaps for stakeholders.